2007
DOI: 10.1097/01.prs.0000287383.35963.5e
|View full text |Cite
|
Sign up to set email alerts
|

Hemifacial Microsomia: Clinical Features and Pictographic Representations of the OMENS Classification System

Abstract: The OMENS system represents the most comprehensive, versatile, objective, and easily adaptable attempt at clinical classification of hemifacial microsomia to date. The authors propose a concise clinical evaluation form using a modified version of the system to promote the use of the OMENS system, to aid in the evaluation of hemifacial microsomia patients, and to assist in data sharing among academic institutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(86 citation statements)
references
References 36 publications
0
81
1
4
Order By: Relevance
“…Results classification based on percentage of fat graft survival regarding grafted volume showed unsatisfactory results for 57.1 percent of the control group and a predominance of excellent results for the experimental group (experimental (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) group: excellent results, 7; control group: excellent, 1; good, 2; unsatisfactory, 4). Through the calculation of relative risk and its variables, it was observed that the experimental group would be seven times as likely as the control group to obtain an excellent result, and an excellent result was attributable to the intervention of supplementation of adipose-derived stromal cells in 85 percent (p = 0.005) ( Table 7).…”
Section: Relative Risk and Its Variablesmentioning
confidence: 96%
See 1 more Smart Citation
“…Results classification based on percentage of fat graft survival regarding grafted volume showed unsatisfactory results for 57.1 percent of the control group and a predominance of excellent results for the experimental group (experimental (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) group: excellent results, 7; control group: excellent, 1; good, 2; unsatisfactory, 4). Through the calculation of relative risk and its variables, it was observed that the experimental group would be seven times as likely as the control group to obtain an excellent result, and an excellent result was attributable to the intervention of supplementation of adipose-derived stromal cells in 85 percent (p = 0.005) ( Table 7).…”
Section: Relative Risk and Its Variablesmentioning
confidence: 96%
“…Inclusion criteria were the presence of unilateral deformity; phenotype M0, M1 or M2, and S1 or S2 according to the Orbit, Mandible, Ear, Nerve, and Soft Tissue-Plus classification 25,26 ; and age between 10 and 35 years. Excluded were patients with previous facial softtissue surgery, patients with absence of lower abdomen fat donor site, and those who refused to participate in the study.…”
Section: Trial Population and Eligibility Criteriamentioning
confidence: 99%
“…1,2 Within an increasingly multicultural patient population in the United States, these skills are as much applicable to the practice of clinical medicine domestically as they are internationally. Moreover, studies have found that international medical opportunities help shape students' choices in eventual medical specialties and career interests.…”
Section: Importance Of International Health Educationmentioning
confidence: 98%
“…Hemifacial microsomia, which is characterized by unilateral hypoplasia of the craniofacial skeleton and overlying soft tissue, presents as a broad spectrum of clinical manifestations. 1 The surgery was an 8-hour craniofacial operation that involved the microvascular reconstruction of the mandible using a fibular osseocutaneous flap. The uniqueness of this operation provided a significant learning opportunity for the medical students and residents who observed a 2-hour portion of the surgery via videoconferencing.…”
Section: Case Report Surgical Team and Proceduresmentioning
confidence: 99%
“…24 • Graphic representation of the OMENS+: a graphic representation of the OMENS+ was introduced in 2007 25 and later modified in 2011, 26 in order to facilitate its understanding in clinical practice, teaching and the standardization of classification of HFM patients.…”
Section: Amendments To the Omensmentioning
confidence: 99%